Electromagnetic Cascades in the Magnetosphere of a Very Young Pulsar: A Model for the Positron Production near the Galactic Center - Mastichiadis, Apostolos; Brecher, Kenneth; Marscher, Alan P. (1987)
A detailed model for positron production by a young pulsar is presented. It is shown that electromagnetic cascades can develop in a young pulsar's magnetosphere, and the model results are applied to the pulsar which is hypothesized to lie near the Galactic center. It is found that such a pulsar would be expected to produce relatively low energy electron-positron pairs with an efficiency rating high enough to explain the observed luminosity of the Galactic center annihilation line. Virtually all of the gamma ray continuum radiation produced in the cascades would be beamed along the magnetic poles of the neutron star, and therefore probably would not be observed from earth. Some observational predictions generated by the proposed model for the Galactic center positron source are given.
Keywords: Annihilation Reactions; Astrophysics; Electron Photon Cascades; Electron-Positron Pairs; ELEMENTARY PARTICLES; Galactic Nuclei; galaxies: nuclei; gamma rays: general; Milky Way Galaxy; Pair Production; Positrons; Pulsar Magnetospheres; Pulsars; RADIATION MECHANISMS